The Influence of Tourist Attraction, Electronic Word of Mouth, and Location on Tourists’ Visiting Decisions at Lotus Tower, Purwokerto, Banyumas Regency - Komalasari, Ayu; Sochimin, Sochimin (Wealth: Journal of Islamic Banking and Finance, 2024)
This study aims to determine how much influence tourist attractions has, electronic word of mouth, and location both partially and simultaneously on the decision to visit tourists at the Teratai Tower Purwokerto, Banyumas Regency. This research is a quantitative research with the type of research that is a causal relationship. The data collection technique was carried out by distributing questionnaires with the population used being tourist who had visited the Purwokerto Teratai Tower tourist attraction. Determination of the population in this study using techniques non probability sampling who uses the method accidental sampling with a sample of 100 respondents who were used as research objects. The data analysis used is multiple linear regression analysis with the SPSS version 20 application. The results of this study indicate that partially and simultaneously the variable tourist attraction, electronic word of mouth, and location has a positive and significant effect on the decision to visit tourists at the Teratai Tower Purwokerto, Banyumas Regency. Suggestions for further research to develop by adding several indicators or other variables related to the decision to visit tourists to a tourist attraction.